KLASIFIKASI KESESUAIAN LAHAN KAKAO MENGGUNAKAN FAKTOR PEMBATAS MAKSIMUM DI KABUPATEN KOLAKA - Syaf, Hasbullah; Arifin, Mahfud; Suriadikusumah, Abraham; Harryanto, Rachmat (Jurnal Agroteknos, 2011)
ABSTRACT The current implementation of land suitability classification of Cocoa is based on the national standard of growing plant. Therefore the implementation of the land use at the specific location was not acceptable. It is important to evaluate the land suitability of the cocoa growing areas. This study was conducted at Kolaka Regency Southeast Sulawesi Province. This research was performed using a survey method based on the observation unit. Which is consist of 93 observation units. The climate, soil and environment observations were following the Soil and Agroclimate Research Centre ( PPTA, 1993); Department of Agriculture (DEPTAN, 1993 dan 2003) and the Indonesian Coffee and Cocoa Research Centre (PPKKI, 2008). The analysis of land suitability is base on the threshold factor using the mínimum. The results showed that the land suitability of the cocoa growing areas according to PPTA dan DEPTAN (1993) were classification full into 76.34% marginal suitable (S3), 12.90% currently not suitable (N1) and 10,75% was permanently not suitable (N2). On the other had based on the DEPTAN (2003) the cocoa growing areas were 83.87% S3 and 16.13% not suitable (N). While according to the PPKKI (2008) the S3 was 63.44% and the N was 36.56%. Key word: land suitability classification and cocoa